Comparative effect of turmeric (Curcuma longa) and durba (Cynodon dactylon) on the healing of surgical wounds in cattle (Bos indicus) - Mamun, Mohammad Abdullah Al; Juyena, Nasrin Sultana; Ali Khan, Md Abu Hadi Noor; Islam, Md Aminul (Asian Journal of Medical and Biological Research, 2018)
Herbal preparations are used traditionally in wound management to promote wound healing process. In Bangladesh, there are limited researches on the use of herbal products to assist healing process. Therefore, this experiment was carried out to exploit turmeric (Curcuma longa) and durba (Cynodon dactylon) pastes in the treatment of surgical wounds in cattle and to study their healing effect on wound sutured with horizontal mattress using nylon. A total of 36 surgical wounds were made in six cattle. Tincture benzoin was used as control group. Follow-up information was recorded from day 0 to day 21 postoperatively. Some morphological characters such as swelling area of wound, elevation of sutured line from the skin surface, width of sutured area and contraction length per week were recorded to determine the healing process of the wounds. Bacteriological and histopathological studies were also performed. All wounds were closely monitored to observe any complications such as swelling, wound dehiscence, suture abscess, local infection and exudation etc. Results showed that Tr. Benzoin seal caused marked tissue reaction in wounds in comparison to turmeric and durba paste. Turmeric paste showed splendid results in the healing of the wounds produced in cattle. Durba paste also has wound healing activity but less effective than that of turmeric. This study could help veterinarians to consider herbal products especially turmeric for healing of wounds with minimum complications. Dissemination of these findings among the farmers may prevent skin degradation caused by the postoperative complications of the wound and thus improve the health status of livestock. Asian J. Med. Biol. Res. June 2018, 4(2): 164-171